Group portrait of the attendees of the Conference of California Committeemen and County Secretaries for the Production and Marketing Administration - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait showing the attendees of the Conference of California Committeemen and County Secretaries for the Production and Marketing Administration, held February 14-16, 1949 in San Jose, California.